30.3k views
1 vote
Recursive rule and a explicit rule for 42,53,64,75,86

User Theozh
by
5.6k points

2 Answers

6 votes

Answer: explicit rule: a_n = 11n+31

Recursive rule: a_n = a_n-1 + 11

Step-by-step explanation: explicit rule formula for an arithmic sequence: a_n = a_1 + (n-1)d

d is the common difference which you find by taking one term and subtracting it by the previous term. For example 53-42= 11 or 75-64= 11 so d is 11

a_1 is the first term in the sequence which is 42 in this case.
substitute into formula and get

a_n = 42 +(n-1)(11) then simplify

= 42 + 11n -11

= 11n -31

Therefore a_n = 11n-31


The formula for a recursive rule for an arithmetic sequence is a_n= a_n-1 + d

Substitute and get a_n = a_n-1 + 11

User Michael Regan
by
5.6k points
5 votes

Answer:

Explanation:

+11

User MyTwoCents
by
6.5k points